Intersection-based geographical perception routing protocol in VANET - Yuqi YANG; Guoan ZHANG; Min WU (Dianxin kexue)
In order to solve the problem of the communication performance of degradation,which caused by multi-intersections in city environment and no sensitivity to individual node movements,an intersection-based geographical perception routing protocol in vehicular Ad Hoc network was proposed.The network gateways select road intersections to form the backbone of the route,ensuring a high probability of communication and meeting delay and bit error rate requirements.Mathematical formula of the average delay and the average number of hops were obtained on the basis of a two-way road model.Simulation results show that the transmission delay of IGPR is smaller,the number of hops of IGPR is less,and the communication performance of IGPR is better compared with the FRGR protocols and VRR protocols.